Development of 34 polynucleotide repeat microsatellites for Chinese lake gudgeon (Sarcocheilichthys sinensis Bleeker, 1871) by transcriptome sequencing. (7th January 2017) - Zhu, C.; Pan, Z.; Wang, H.; Wu, N.; Chang, G.; Ding, H.
Summary: A total of 34 novel polymorphic polynucleotide repeat microsatellites were developed for Sarcocheilichthys sinensis through transcriptome sequencing. Results of polymorphism characterization in a test population showed that the number of alleles of these loci ranged from 2 to 12, averaging 5.2 alleles per locus. Observed and expected heterozygosity varied from 0.0333 to 0.9667 and from 0.0333 to 0.8825, respectively. Twenty‐seven loci were proven to be highly informative because the values of their polymorphism information contents were greater than 0.5. These novel polymorphic microsatellite markers would be useful tools for further population and conservation genetic studies of S. sinensis .